Возникновение и становление мультимедийных площадок и конвергентной журналистики Республики Армения и Российской Федерации - Сафарян, Арман (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Հոդվածում քննվում են ՀՀ և ՌԴ մուլտիմեդիային լրագրության պատմական նախատիպերը և կայացման փուլերը։ Հայաստանի և Ռուսաստանի մուլտիմեդիային լրագրության մեկնարկը կարելի է համարել “.ru” и “.am” դոմենների գրանցումը՝ 1994 թվականին։ The article examines the historical prototypes and stages of the formation of multimedia journalism in the Republic of Armenia and the Russian Federation. We could start the countdown of the history of multimedia journalism in Armenia and Russia beginning from 1994 (since the registration of the ‘.ru’ and ‘.am’ domains).
Keywords: Мультимедийная журналистика; Конвергентная журналистика; Гражданская журналистика